PRODUKTIVITAS BONGKAR MUAT KAPAL RO-RO PT ASDP INDONESIA FERRY - Rr Endang Wahyuni; Mega Silvia; Deslida Saidah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
PT. ASDP Indonesia Ferry (Persero) is a state-owned company specialized on crossing and port sector that is responsible for organizing ferry transportation and ports effectiveness and efficiency. To be able to give an excellent service, the company has to maintain its’ loading and unloading of Ro-Ro ship productivity in a high-quality level. The objective of this research is to find out the improvement of Ro-Ro ship loading and unloading productivity, target and achievement of Ro-Ro ship loading and unloading productivity during 2012-2014.  The result of the research shows that during the period of 2012 to 2014 the Ro-Ro ship loading and unloading productivity result starting in the first semester of 2012 to the second semester of 2014 shows that not all of the targets determined by the company are accomplished. The trend analysis shows that the productivity of Ro-Ro ship loading and unloading was fluctuating during the period.